Comparison of the impact of fast charging on the cycle life of three lithium-ion cells under several parameters of charge protocol and temperatures. (1st February 2021) - Mathieu, Romain; Briat, Olivier; Gyan, Philippe; Vinassa, Jean-Michel
Highlights: Study of the impact of fast charging on battery ageing at several temperatures. Comparison of three cells with different electrode materials and energy densities. Sensitivity to charge, voltage and temperature explained by non-intrusive analyses. Different dominant degradation mechanisms occur depending on electrode materials. Several strategies can improve the trade-off between charge time and lifetime. Abstract: Fast charging of lithium-ion batteries is crucial for electric vehicles. As the charge current is a known degradation factor, assessing the impact of fast charging on battery ageing under several operating conditions is necessary to derive usage strategies for system integrators. To bridge existing knowledge gaps, this article reports on a comparative experimental ageing study in fast charging conditions. Three cells, differing in their materials and energy densities, were investigated. The impacts of the following three parameters are compared on these cells: charge current, end-of-charge voltage, and ambient temperature. The results reveal that the impact of fast charging on cycle life strongly depends on battery materials and internal design. The degradation of two of the cells significantly increased when the charge current and voltage increased, whereas that of the third cell was nearly independent of these parameters. While considering thermal conditions, the ageing of each cell was minimised at a different temperature, either cold, moderate, or warm. An analysis of degradation root causes indicates that distinct dominant degradation mechanisms occurred depending on the cell materials. The cells with higher energy density had a lower cycle life (between 100 and 900 cycles) than the most high-power cell (more than 1700 cycles). Experimental results allow the identification of three strategies for reducing charging time while minimising battery degradation. These strategies present several contributions to the design of energy storage systems for electric vehicles, including the choice of a cell, design of thermal management systems, and design of optimised fast charging protocols.